Analisis Kinerja Struktur Data Kd-Tree Pada Metode K-Nearest Neighbors - Yuan Lukito (RJOCS (Riau Journal of Computer Science), 2016)
K-Nearest Neighbors is a commonly used classification technique that can be categorized into instance-based classification method. The performance of KNN is mostlydetermined by the size of the training data. This research compared and analyzed KD-Tree andArray data structures on KNN implementation. Dataset used in this research has largemultidimensional features. From the experiment conducted we can conclude that KD-Tree datastructure has better and relatively stable performance compared to Array data structure.